Рецензія. Нове розуміння теорії концептуальної метафори: Kövecses, Zoltán. (2020). Extended Conceptual Metaphor Theory - Лехнер, Ілона; Кордонець, Олександр (Східноєвропейський журнал психолінгвістики, 2021)
The author of the reviewed book is Zoltán Kövecses, a renowned cognitive linguist from Central and Central-Eastern Europe, but lesser-known from the Ukrainian academic literature. He is Emeritus Professor at Eötvös Loránd University (Budapest, Hungary). He is one of the four editors of the international scholarly journal, Metaphor and Symbol, and he also serves on the advisory board of Cognitive Linguistics and several other international professional journals. He carried out research and taught as visiting lecturer at several world-famous American and European universities (e.g. the University of Nevada at Las Vegas, Rutgers University, University of Massachusetts at Amherst, the University of California at Berkeley, Hamburg University, and Odense University).Cognitive linguistic bases of the conceptual metaphor theory (CMT) were laid down by Lakoff and Johnson (1980) in their book Metaphors We Live By. This was the basic work on which cognitive linguists based their further research, supplementing and refining the original ideas of linguists who can be called the fathers of this theory. In the preface, the author testifies to the theory underlying the book as follows: “I believe CMT is a theory that can provide powerful and coherent explanations for a variety of aspects of metaphor. In my judgment, no other theory is as comprehensive as CMT. It took almost forty years for CMT to reach this stage. It’s been steadily developing thanks to the many great scholars who played key roles in making it what it is today. I see the present book as just another contribution to this line of development – as an organic part of all the efforts that have been put into making it better” (p. xi).Besides the preface, the book is divided into eight chapters, having a special structure. In the preface, the author outlines the book, its structure and basic concept, and mentions by name all those who helped the development of his theory with their thoughts and research. He highlights two linguists in particular: “Two people have played very special roles in the course of my career as a metaphor researcher. Ray Gibbs has always been available to discuss various issues related to the field and he and his work gave me a huge amount of encouragement and inspiration. And last but definitely not least, without George Lakoff I could not have and would not have done any of my work on metaphor” (p. xiii). In the first chapter, the author presents the traditional conceptual metaphor theory, which is “standard” in his formulation, and raises some of the questions that form the basis of the following five chapters. The titles of Chapters 2-6 are thus questions that have been articulated in the author in the course of several years of research activity in connection with the theory. These are the suggestions responding to which will lead us to an extended version of the conceptual metaphor theory. Relying on his own research and that of the cognitive linguistic society, the author justifies the raison d'être of the question in each chapter and illustrates his line of thought with linguistic examples, tables and figures. The rest of the book contains two summarizing, integrating chapters (7-8), in which the author outlines the extended CMT, and then as a conclusion answers the questions discussed in the book. The publication ends in a long list of references and an index.In the first chapter (A Brief Outline of “Standard” Conceptual Metaphor Theory and Some Outstanding Issues), the author discusses the basics of CMT in detail. He emphasizes that there is no full agreement among cognitive linguists on the interpretation of the theory, but in this chapter, he focuses on those elements and features that are predominantly interpreted similarly by metaphor researchers. At the end of the chapter, the author lists problems that have arisen over the years and are waiting to be solved.The title of the second chapter (The Abstract Understood Figuratively, the Concrete Understood Literally, but the Concrete Understood Figuratively?) projects its content, its central issue, the nature of meaning. The author considers the distinction between concrete and figurative meaning to be particularly important, since, according to the definition of “standard” theory, the conceptual metaphor is based on precisely this distinction. In this chapter, the author argues that even our most concrete experiences can be interpreted figuratively and not just literally. We have a lot of concepts that we have taken over from previous generations, we understand them literally, and use them to conceptualize further abstract concepts. The notion of figuratively interpreting even our basic concrete experiences raises important questions for conceptual metaphor theory, which the author answers in turn in the chapter and then draws the following conclusion: “Thus, both concrete and abstract concepts have both embodied content ontology and figurative construal (i.e., figuratively constructed understanding) – but in different proportions. In conceptual metaphors, we have predominantly content-ontology-based concepts as source domains and predominantly figuratively-construed concepts as target domains. There are probably no pure ontology-content-based concepts and no pure figuratively-construed concepts” (p. 33).In the section entitled Direct or Indirect Emergence, the author discusses what forms the basis of conceptual metaphors. He contrasts two views: the primary metaphors are based on bodily experience, from which complex metaphors are constructed; every metaphor is built on metonymy. Basically, therefore, the author sheds light on the more nuanced relationship between the conceptual metaphor and metonymy in this chapter: “I […] suggest that many metaphors (of the correlational kind) derive from metonymies, that is, they have a metonymic basis. What distinguishes my position from the view of the other proponents in the group that favours a metonymy-based emergence for many metaphors is that I attempt to establish the relationship between metaphor and metonymy by relying on several particular characteristics of the conceptual system, as we know it today” (p. 35).In the fourth chapter (Domains, Schemas, Frames, or Spaces?), Kövecses analyses in detail the differences between the concepts listed in the title and their significance in the CMT. He admits that cognitive linguists also often have difficulty figuring out how to unequivocally identify which conceptual unit or structure is involved in conceptual metaphors. According to Kövecses, the solution lies in thinking of conceptual metaphors as the ones that simultaneously involve conceptual structures, or units, on several distinct levels of schematicity. He believes that four levels can be distinguished (“the level of image schemas, the level of domains, the level of frames, and the level of mental spaces (in addition to the linguistic level of the actual utterances in which the metaphors are instantiated”) (p. 51)), among which there is a hierarchical relationship. Each metaphor can be analysed at any level.In the fifth chapter (Conceptual or Contextual?), the author explains the role of language users’ local and global contexts in metaphorical conceptualization. The original standard CMT emerged primarily as a cognitive theory that ignored the contextual effect. As a result, linguists in many cases were unable to explain, or could explain only with difficulty the emergence of certain conceptual and linguistic metaphors. According to the contextualist version of conceptual metaphor theory, three important questions arise, which the author answers in the chapter: (1) What are the elements of (metaphorical) meaning making?; (2) What are the most common contextual factors that play a role in the use and creation of metaphors?; and (3) What is the cognitive mechanism through which contextual factors actually produce metaphors in natural discourse? (p. 94).The question in the next chapter (Offline or Online?) is that during metaphorical conceptualization, conceptual metaphors are created online in real discourse, that is, we are constantly creating them, or they are present in our conceptual system and retrieved in certain discourses. The “standard” CMT has been the subject of most criticism for not examining conceptual and linguistic metaphors in living language speech, but on the basis of the linguistic material of databases and dictionaries. Kövecses sees the solution to the problem in the multi-level hierarchical system outlined in Chapter 4. “In the «standard» view of CMT, researchers work on the levels of image schema, domain, and frame. These are conceptual structures that are decontextualized patterns in long-term memory that can account for metaphorical meaning in the most general ways., (while) […] online metaphorical activity necessarily makes use of the conceptual structure of mental spaces” (p. 117). The conceptual metaphor can thus be both online and offline: during metaphorical conceptualization, we operate offline metaphors retrieved from long-term memory online in the mental spaces of working memory. This view allows us to take into account the diversity of mental activities related to metaphors.After asking the questions discussed in the previous five chapters, in the next one (The Shape of the Extended View of CMT), Kövecses outlines the theory he has extended, naming its new elements. The extended theory is basically organized around two main questions: (1) Why does the speaker choose (not consciously) that particular metaphor in a given context? (2) How can the speaker create and the listener interpret the meaning expressed by the conceptual metaphor? In addition to elaborating on the two questions, the chapter also discusses the difference between embodied and discourse metaphor, the types of metaphorical meaning and metaphors, and then itemizes the characteristics of the new approach to the theory, feeding back to the responses given to the questions discussed in previous chapters.In the last chapter (By Way of Conclusion: Responses to the Five Questions), the author draws conclusions, evaluates the answers to the questions asked, and explains what overlaps can be detected between the extended CMT and different theories (blending, deliberate metaphor theory, structure-mapping theories, relevance theory). Finally, he compares the extended metaphor theory to the dynamic systems view of metaphor developed by Ray Gibbs (2017), according to which “metaphoric activity is a dynamic, self-organized process” and considers metaphor “as an emergent product of multiple constraints operating along different time scales” (p. 181). The similarity between the two theories is discussed in detail.In summary, the book offers new insight into the subject of conceptual metaphor, updating the previously grounded theory. It relates conceptual metaphor theory to current theories of cognitive linguistics and clarifies a number of issues that metaphor researchers have raised over the past few decades. Relying on traditional CMT, the chapters provide suggestions for an extended conceptual metaphor theory, including a discussion of whether literal meaning exists at all, whether conceptual metaphors are conceptual and / or contextual, and whether they work offline and online at the same time. Cognitive linguistics is a new and continuously evolving linguistic discipline whose research findings are constantly updated. This book was also intended to fulfil this goal, which does not only enrich the knowledge of researchers of metaphorical cognition but can also broaden the perspectives of those interested in literary studies.